MODEL FOR SETTLING REGIONAL ELECTION DISPUTES THROUGH ELECTION COURTS - Sri Sumanta; Natangsa Surbakti; Nunik Nurhayati; Arief Budiono (RADJA PUBLIKA, 2026)
The German Constitutional Court was the first to implement constitutional complaints. It can serve as comparative models for granting the Indonesian Constitutional Court the authority to adjudicate constitutional complaints in the context of strengthening the fulfillment of economic, social, and cultural rights. The problem can be formulated as follows: How is the description of disputes over regional election results through election courts? And how effective is the resolution of disputes over regional election results through election courts? This research is a sociological juridical study, so the approaches used to solve the problems in this research are doctrinal and non-doctrinal approaches. Several key issues related to regional elections include the lack of good quality of regional election regulations; Regional General Elections Commission, the Elections Supervisory Committee, including the police, the prosecutor's office, and the courts; regional election disputes, including administrative disputes, election crimes, and election result disputes. To ensure effective and high-quality election dispute resolution, three stages of the regional election process must be regulated and implemented comprehensively and thoroughly. Criminal disputes must be resolved expeditiously by the relevant legal authorities before the vote count begins or at the latest before the election winner is declared.